IMPLEMENTASI QANUN ACEH NOMOR 11 TAHUN 2018 TENTANG LEMBAGA KEUANGAN SYARIAH DAN KAITANNYA DENGAN PRAKTIK RIBA DI MASYARAKAT DESA ALUE DAWAH - Perdana, Putri; Ruhendi, Ateng; Sadi'ah, Diah Siti (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2021)
Qanun on Islamic financial institutions is one way for the Aceh government to present a community economy that is in accordance with Islamic teachings. However, the people of Alue Dawah village, Babahrot sub-district, still carry out muamalah practices that are not in accordance with Islamic teachings, these practices are transactions that still contain elements of usury. This study aims to determine the understanding of the people of Alue Dawah village that there is usury, to find out the types of usury practices that are often carried out by the people of Alue Dawah village and to know the application of Aceh Qanun No. 11 of 2018 on the practice of usury in the village community of Alue Dawah. This study uses a qualitative method with a descriptive analytical approach and normative juridical, to collect data in the Alue Dawah village community and describe or explain what is from the results of the research and synchronize the qanun of Islamic financial institutions so that it can be compiled in written form (narrative), interpreted and analyzed. The results show that the people of Alue Dawah village can understand usury and its law from various perspectives, although they cannot explain it systematically. The practice of usury that is often carried out by the people of Alue Dawah village is usury qard and usury jahiliyah, while the current application of the qanun of Islamic financial institutions has not shown any connection with usury practices carried out by the people of Alue Dawah village. Qanun Lembaga Keuangan Syariah merupakan salah satu cara pemerintah Aceh menghadirkan ekonomi syariah di tengah – tengah masyarakat Aceh. Kenyataannya, masih ada desa yang tidak melaksanakan Qanun tersebut. Masyarakat Desa Alue Dawah kecamatan Babahrot masih melakukan praktik riba. Penelitian ini bertujuan untuk mengetahui pemahaman masyarakat Desa Alue Dawah terhadap riba, mengetahui jenis praktik riba yang sering dilakukan oleh masyarakat Desa Alue Dawah dan mengetahui penerapan Qanun Aceh No. 11 Tahun 2018 terhadap praktik riba di masyarakat Desa Alue Dawah. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif analitis dan yuridis normatif. Penulis mengumpulkan data, sinkroniasasi dengan Qanun, menganalisis, dan memaparkan dalam bentuk naratif. Hasil penelitian menunjukkan bahwa sebenarnya masyarakat Desa Alue Dawah mengetahui jenis – jenis riba dan hukumnya, namun tidak dapat memahami dan menjelaskan secara sistematis. Oleh karena itu, masyarakat masih melakukan praktik riba. Praktik riba yang sering dilakukan masyarakat Desa Alue Dawah ialah riba qard dan riba jahiliyah. Kesimpulannya, Qanun Lembaga Keuangan Syariah belum banyak dipahami dan dilaksanakan oleh masyarakat Desa Alue Dawah.